MODIFIKASI DAN UJI TEKNIS ALAT PEMBERSIH BIJI JAGUNG DENGAN KOMBINASI SISTEM AYAKAN BERGOYANG DAN HEMBUSAN ANGIN - Kahar Drakel; Freeke Pangkerego; Dedie Tooy (Universitas Sam Ratulangi, 2018)
Abstract Corn (Zea mays L) is one of the cereal plants that grows almost all over the world and is classified as a species with large genetic variability. In Indonesia corn is the second staple food after rice. Besides that, corn can be used as animal feed ingredients and industrial raw materials (Fadhullah Muhammad 2016). Sieving is the separation of the mixture of solid particles that have various sizes of material using a sieve. The sieving process is also used as a cleaning tool, the separator of waste which is different in size from the raw material. The purpose of this study was to modify and technically test the corn seed cleaning system using the electro motor sway and different air flow speeds using a fan. This research has been carried out in the Agricultural Engineering Workshop, Agriculture Technology Department of the Faculty of Agriculture Unsrat for 3 months from May to July 2018, including the making of sieving tools, implementation of sieving experiments and analysis of research data. This study includes the modification and technical testing of corn seed cleaning equipment with a combination of swaying and wind blowing sieve systems, using 3 different air flow rates from different fans with 3 (three) replications, namely: 1. Air flow velocity 1.3 m / s ( A), 2. Air flow velocity 2.1 m / s, (B), and 3.Air flow velocity of 3.5 m / s (C). The speed of air flow in this study is not the same level, only adjusting the speed of the fan (fan) made by the factory Â Keywords: Modification of tools, sway sieve system, wind gusts